Microbiological quality assessment of beef meat in laghouat region - Benmouiza, Mohammed; Derbal, Ibrahim; Djokhdem, Laid, Directeur de thèse; Benarfa, Mouna, Directeur de thèse (Laghouat : Université Amar Telidji - Département d'agronomie, 2024)
The beef meat market in Algeria has seen a significant increase recently. However, the increased importation of beef and otherwise materials and equipment as well as consumer awareness in Algeria may lead to challenges related to microbial contamination due to the increased handling of meat which can lead to health risks for consumers. The objective of this study has enabled us to provide a quantified microbiological quality assessment of beef meat in laghaout region of the levels of contamination by spoilage indicator germs (total aerobic mesophilic flora: FAMT), faecal contamination (thermotolerant coliforms) and Staphylococcus aureus contamination.the Methodology is to carry out microbiological analyses of 15 beef meat samples taken from 5 selected butchers' shops on a 3 days period, in the regain of laghouat. During our study, we noted that that the number of butcheries with a number of microorganisms statistically exceeding (p<0. 05) the acceptance limit set by the standard is One for AFMT, three for staphylococci, and for thermotolerant coliforms all butcheries It did not exceed the acceptance limit and the other butcheries, the enumeration of flora sought indicated statistically lower loads (p<0.05) compared to the microbiological criteria set by regulation, poor handling during meat preparation operations leads to very high levels of contamination. These contaminations can cause various serious health diseases and rapid meat spoilage, thus limiting its shelf life. A complementary study was conducted to obtain indices of consumer preferences for beef products. A questionnaire was developed for this purpose. The questionnaire included 17 questions to gather information on demographic and social variables also consumer behavior, perceptions of beef, and beef consumption preferences. The results show that the local consumer is somewhat familiar with these products and their behavior reflects the consumption habits of the region. This necessitates a thorough study in the future concerning this topic and the significance of recommending Configuring workers responsible for meat handling in good hygiene practice. in perspective, it would be useful to control the microbiological quality of meats at various levels from slaughterhouses to butchers to better understand and identify the origins of contamination and microbiological contamination issues.